Analysis of National QR Code Payment Systems: Practices in 3 Developing Countries (Indonesia, Nigeria, and India) - Andi Asrihapsari; Ika Swasti Putri; Arinze E. Anaege (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
This study explores the payment system practices using national quick response codes (QR codes) in three developing countries—Indonesia, India, and Nigeria—which are members of the World Trade Organization (WTO). Using a systematic literature review (SLR) approach guided by the PRISMA 2020 protocol, this study analyzed 15 peer-reviewed articles to examine the implementation of QR code-based payment systems. Specifically, the review evaluated trends in national policy practices, geographical focus, research methodologies, journal classifications, and theoretical frameworks employed. Although the study adopted a qualitative SLR methodology, it drew analytical insights from the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). A key finding reveals that national QR code payment systems have been implemented in Indonesia (QRIS), India (BharatQR), and Nigeria (NQR). The goal of implementing national QR code systems is to support financial inclusion, transaction efficiency, and the transition to a cashless society. This study identifies a research gap related to security issues, data privacy, and the macroeconomic impact of QR code payments. This study provides direction for future studies by recommending a mixed-methods approach, cross-cultural exploration, and review of national policies as part of developing an inclusive and sustainable digital payment system.